Fostering Resilience and Adapting to Climate Change in the Canadian North— Implications for Infrastructure in the Proposed Canadian Northern Corridor - S. Jeff Birchall; Sarah Kehler; Nicole Bonnett (The School of Public Policy Publications, 2022)
The Canadian Northern Corridor (CNC) has been proposed to overcome gaps in the northern transportation system that limit social and economic development in the Canadian North (Fellows et al. 2020). Intended to be a multimodal transportation right- of-way through Canada’s North, the CNC seeks to capitalize on shifting global markets and increased access to northern resources (Pearce et al. 2020; Fellows et al. 2020). However, transportation infrastructure has remained constrained across northern Canada. Significant challenges exist for northern infrastructure due to isolation, restricted access and extraordinary environmental conditions — all of which climate change is projected to radically intensify (Palko and Lemmen 2017; Pearce et al. 2020).